2019
DOI: 10.21203/rs.2.12462/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicenter investigation of pediatric gastrointestinal tract magnets ingestion in China

Abstract: Purpose: To describe the incidence and management of gastrointestinal tract Buckyball magnets ingestions in a multicenter Chinese pediatric patient population, and discuss the preventive measures. Methods: Medical records of 74 pediatric patients from 9 large Chinese hospitals during the past 10 years, who were diagnosed as buckyball magnets ingestion and got invasive treatment, were retrospectively studied. The follow-up was through telephone and outpatient service to estimate the post-surgery condition. Info… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…We noted that all incidences of ingestion of foreign objects occurred after 2018. This is similar to a 2020 study that found recent increase in pediatric gastrointestinal tract magnets ingestion in China [8]. Second, colorectal adenocarcinoma led to 2 colon perforations in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We noted that all incidences of ingestion of foreign objects occurred after 2018. This is similar to a 2020 study that found recent increase in pediatric gastrointestinal tract magnets ingestion in China [8]. Second, colorectal adenocarcinoma led to 2 colon perforations in this study.…”
Section: Discussionsupporting
confidence: 92%
“…First, despite literature reporting peak incidence of colon perforation due to foreign object ingestion being between 6 months to 3 years [7], of the 5 incidences, only 1 patient was younger than 2 years old. While most objects can be passed out of the alimentary tract without incident, 1-5.6 % result in colon perforation [7,8]. We noted that all incidences of ingestion of foreign objects occurred after 2018.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the USA government has forced toy companies to recall certain magnetic toys. Accordingly, in some areas of the USA, the incidence of multiple magnet ingestion has decreased 6 . In China, although there are warning labels on the toy packages, a recent multicenter investigation shown that the incidence of multiple magnet ingestions is increasing 7 .…”
Section: Discussionmentioning
confidence: 99%